Relationship Between Smoking Habits and Hypertension Incidence in Men Aged 40 Years at Rambung Health Center, Tebing Tinggi City - Riada Mareny (International Journal of Public Health Excellence (IJPHE), 2023)
Hypertension is also one of the health problems found in the Indonesian population. There are many risk factors that can cause hypertension, including smoking, genetics, obesity, stress, salt intake, and exercise. There is a problem of smoking habits (number of cigarettes smoked, type of cigarette smoked (smoked, duration of smoking) with the incidence of smoking in men aged ≥ 40 years at the Rambung Health Center, Tebing Tinggi City. A descriptive analytic research design with a cross sectional study design with a sample of 81 men aged ≥40 years. The research found that there was a relationship between smoking habits and the incidence of smoking at the Rambung Community Health Center, Tebing Tinggi City. Using the chiaware test, it was stated that there was a relationship between smoking habits and the incidence of hypertension in PNA ≥40 years at the Rambung Health Center, Tebing Tinggi City. For respondents, it is expected that smoking users reduce the number of cigarettes smoked or can avoid hypertension or at least be able to control hypertension that they already suffer.